Age-related and seasonal change in serum osmolarity and water intake in a healthy population. (13th November 2019) - Nishikawa, T; Miyamatsu, N; Higashiyama, A; Nishida, Y; Kubota, Y; Hirata, T; Sugiyama, D; Kuwabara, K; Miyamoto, Y; Okamura, T
Abstract: Background and aim: Few studies have clarified the seasonal and age-related change of serum osmolarity and water intake, which is thought to be associated with heat stroke and ischemic stroke. We investigated the association between them in a healthy population. Methods: We conducted a cross-sectional study using database from Kobe Orthopedic and Biomedical Epidemiologic (KOBE) Study. Among 1138 healthy Japanese participants in the baseline survey, 1010 (women 704 and men 306) participants were eligible for the present study. Daily non-alcohol drink (NAD) intake was estimated according to food frequency questionnaire. Alcohol beverage and water in the meal or soup were excluded from the counting. Serum osmolarity (Osm/L) was calculated by Worthley's formula: 2 (serum sodium (mEq/L)) + (blood urea nitrogen (mg/dL))/2.8 + (glucose (mg/dL))/18. The seasons the surveys were conducted were categorized into 4 groups, March-May (Spring), June-August (Summer), September-November (Autumn), and December-February (Winter). The association between serum osmolarity and daily NAD intake was analyzed using linear regression models. Results: The seasonal change was observed in the serum osmolarity and daily NAD intake; serum osmolarity increased in spring and summer and daily NAD intake increased in summer. The serum osmolarity increased by aging in any seasons, while daily water intake didn't. There was no significant association observed between serum osmolarity and the daily NAD intake, even after adjusting for sex, age, and season. Conclusions: Serum osmolarity showed seasonal and age-related changes, but the serum osmolarity in subjects who had the daily habit of high NAD intake was not necessarily low. Key messages: Serum osmolarity increased by aging and in spring and summer. Serum osmolarity was not associated with non-alcohol drink intake.